Synthesis and characterization of magnetic and microwave absorbing properties in polycrystalline cobalt zinc ferrite (Co0.5Zn0.5Fe2O4) composite - A. N., Hapishah; M., M. Syazwan; Hamidon, M. N. (Springer, 2018)
In this research work, magnetic and microwave absorption loss and other response characteristics in cobalt zinc ferrite composite has been studied. Cobalt zinc ferrite with the composition of Co0.5Zn0.5Fe2O4 was prepared via high energy ball milling followed by sintering. Phase characteristics of the as-prepared sample by using XRD analysis shows evidently that a high crystalline ferrite has been formed with the assists of thermal energy by sintering at 1250 °C which subsequently changes the magnetic properties of the ferrite. A high magnetic permeability and losses was obtained from ferrite with zinc content. Zn substitution into cobalt ferrite has altered the cation distribution between A and B sites in spinel ferrite which contributed to higher magnetic properties. Specifically, Co0.5Zn0.5Fe2O4 provides electromagnetic wave absorption characteristics. It was found that cobalt zinc ferrite sample is highly potential for microwave absorber which showed the highest reflection loss (RL) value of − 24.5 dB at 8.6 GHz. This material can potentially minimize EMI interferences in the measured frequency range, and was therefore used as fillers in the prepared composite that is applied for microwave absorbing material.